Dampak Tata Kelola Lembaga Terhadap Kinerja Lembaga di PPSDM Aparatur - Mulyana, Agus (JURNAL APARATUR, 2020)
The aim of this study was to determine how well the implementation of the principles of the governance institution and its relation to the performance on PPSDM Aparatur. The principles of governance is the principle of transparency, independence, accountability, responsibility, and fairness. The method used in this research is quantitative research methods. In assessing the implementation of the principles ofgovernance institutions and its effect on performance, the authors uses quetionare as a primary data. The analysis results of the implementation of governance institution on PPSDM Aparatur based on questionnaires reached 74.2 percent and the results of the dependent variable performance scores 76 percent, both are included good category. The partial results of hypothesis testing showed that each independent variable on the dependent variable affects the performance of the institution. Variables affectthe principle of transparency by 73.8%, amounting to 72.9% the independence principle, the principle of accountability by 84%, amounting to 95.6% accountability principle, and the principle of fairness by 79.9%. And the influence of the independent variable most dominant or most influence on the performance of the institution is the responsibilityvariables. ABSTRAKTujuan dari penelitian ini adalah untuk mengetahui seberapa baik implementasi prinsip-prinsip tata kelola lembaga dan hubungannya terhadap kinerja pada PPSDM Aparatur. Prinsip-prinsip tata kelola yang digunakan adalah yakni prinsip keterbukaan, kemandirian, akuntabilitas, pertanggungjawaban, dan kewajaran. Metode penelitian yang digunakan dalam penelitian ini adalah metode penelitian kuantitatif. Dalam menilai implementasi prinsip- prinsip tata kelola lembaga dan pengaruhnya terhadap kinerja, penulis menggunakan kuesioner sebagai data primer. Hasil implementasi tata kelola lembaga di PPSDM Aparatur berdasarkan kuesioner mencapai 74.2 persen dan hasil dari variabel terikat kinerja mendapatkan nilai 76 persen, keduanya termasuk dalam kategori baik. Adapun hasil uji hipotesis secara parsial menunjukan bahwa setiap variabel independen berpengaruh terhadap variabel dependen kinerjalembaga.Variabel prinsip keterbukaan berpengaruh sebesar 73.8%, , prinsip kemandirian sebesar 72.9 %, prinsip akuntabilitas sebesar 84 %, prinsip pertanggungjawaban sebesar 95.6 %, dan prinsip kewajaran sebesar 79.9 %. Dan pengaruh variabel independen yang paling dominan atau paling besar pengaruhnyaterhadap kinerja lembaga adalah variabel pertanggungjawaban.